Positive electrode active material and preparation method and application thereof
By grinding and mixing different iron phosphate precursors, a high-pressure density positive electrode active material was prepared, which solved the problem of unsatisfactory electrochemical performance of the battery in the prior art and achieved higher battery performance.
Patent Information
- Application Number
- CN202411972304.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, although the compaction density of the positive electrode active material has been improved, the electrochemical performance of the battery is not ideal enough, and it is necessary to develop a positive electrode active material that can improve the compaction density and improve the electrochemical performance of the battery.
The positive electrode active material with high compaction density was prepared by grinding the first iron phosphate precursor and the second iron phosphate precursor to a specific particle size, and then mixing and spray drying and sintering. The method includes steps such as low-temperature sintering, crushing, pulsed high-temperature sintering and second crushing to optimize the particle size distribution and structure of the material.
A positive electrode active material with high compaction density is achieved, which significantly improves the electrochemical performance of the battery, including improved discharge specific capacity, more stable capacity retention and better thermal stability.
Smart Images

Figure CN119890254A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a positive electrode active material and a preparation method and application thereof. Background Art
[0002] Lithium iron phosphate (LiFePO4) is the most widely used positive electrode material in lithium-ion power and energy storage batteries. In order to meet the market's demand for higher energy density of lithium-ion batteries, it is necessary to develop LiFePO4 materials with higher specific energy. According to: theoretical volume energy density = mass of positive electrode active material on the positive electrode sheet per unit volume of the battery × working voltage of positive electrode active material × mass specific capacity, therefore, the energy density of positive electrode active materials can be improved from three aspects: working voltage, compaction density and mass specific capacity of the material. The working voltage of the material is determined by the crystal structure, which is an intrinsic property of the material and changes very little. Therefore, the specific energy of the positive electrode active material should be improved from two aspects: compaction density and specific capacity. The compaction density of the positive electrode active material powder is related to the particle size. Generally speaking, the compaction density of the positive electrode active material powder with large particles is higher than that of small particles. However, blindly increasing the particle size of the positive electrode active material particles to increase the compaction density of the material will result in significant degradation of the electrical properties of the material. Therefore, using large and small particle grading is one of the methods to increase the compaction density.
[0003] In the prior art, although the compaction density of the positive electrode active material has been improved, the electrochemical performance of the battery is still not ideal. Therefore, it is very important to develop a positive electrode active material with high compaction density and improved electrochemical performance of the battery. Summary of the invention
[0004] In view of the above problems, the present application provides a positive electrode active material and a preparation method and application thereof. The preparation method described in the present application is conducive to obtaining a positive electrode active material with a high compaction density, and the obtained positive electrode active material can improve the electrochemical performance of the battery.
[0005] In a first aspect, the present application provides a method for preparing a positive electrode active material, the preparation method comprising the following steps:
[0006] (1) mixing a first iron phosphate precursor, a first lithium source, a first carbon source and a first conductive agent to form a first slurry;
[0007] Mixing a second iron phosphate precursor, a second lithium source, a second carbon source, and a second conductive agent to form a second slurry;
[0008] The primary particle size of the first iron phosphate precursor is 100 nm to 110 nm;
[0009] The primary particle size of the second iron phosphate precursor is 40nm to 100nm;
[0010] (2) grinding the first slurry and the second slurry independently until the Dv50 particle size of the solid matter in the first slurry is 0.65 μm to 0.75 μm (e.g., 0.65 μm, 0.66 μm, 0.68 μm, 0.7 μm, 0.72 μm, 0.74 μm, 0.75 μm, etc.), and the Dv50 particle size of the solid matter in the second slurry is 0.20 μm to 0.30 μm (e.g., 0.20 μm, 0.22 μm, 0.24 μm, 0.26 μm, 0.28 μm, 0.30 μm, etc.);
[0011] (3) After mixing the ground first slurry and the second slurry, spray drying and sintering are performed to obtain the positive electrode active material.
[0012] In the present application, primary particles refer to unagglomerated particles, which are the smallest entities in the powder that can be separated and exist independently.
[0013] The Dv50 particle size refers to the particle size value corresponding to 50% of the cumulative volume in the particle distribution. Specifically, Dv50 means that among all the particles, half of the particle volume is less than or equal to this particle size, and the other half of the particle volume is greater than this particle size. The Dv50 particle size in this application is obtained by testing using the laser diffraction method. The specific process is: disperse the sample in a suitable medium to make a uniform suspension, then let the laser beam pass through the suspension, measure the intensity distribution of the scattered light, and finally perform data processing and analysis through computer software to obtain the particle size distribution result.
[0014] In the technical scheme of the implementation mode of the present application, a first iron phosphate precursor is selected, that is, a power-type iron phosphate precursor, the primary particles have a uniform and round particle size, the internal pore size is well connected, and the electrochemical performance can be effectively exerted. Secondly, the specific surface energy is small, it is not easy to melt each other, and it is easy to maintain the individual growth of the particles; the first iron phosphate precursor forms a first slurry, and the Dv50 particle size of the solid is ground to 0.65μm~0.75μm, which is more conducive to the transmission of lithium ions and improves the discharge specific capacity. A larger particle size will cause the particles to be uneven after sintering, affecting the capacity; a smaller particle size will cause the slurry to agglomerate and be difficult to disperse, and the particles will be uneven after sintering, affecting the transmission path of lithium ions.
[0015] A second iron phosphate precursor, i.e., a compacted iron phosphate precursor, is selected to form a second slurry. i.e., a compacted iron phosphate precursor has a large specific surface energy and is easy to melt with each other and agglomerate to form larger particles. The second iron phosphate precursor is used to form a second slurry and is ground to a Dv50 particle size of 0.20 μm to 0.30 μm, so that the particles can better melt and grow with attachment. However, a larger particle size will not only lead to an unsatisfactory grading effect, but also affect the insufficient contact between particles and affect the electrochemical properties. A smaller particle size will lead to particle breakage during sand milling, affecting the physical and chemical properties.
[0016] The first slurry and the second slurry are ground and mixed, and then mixed in the liquid phase. The components can be evenly mixed, and the particle size and particle size distribution of large and small particles of different components are easy to control; at the same time, their own fluidity and stacking state are conducive to improving the powder compaction density of the positive electrode active material lithium iron phosphate, and can improve the electrochemical performance of the battery.
[0017] Preferably, in step (1), the chemical formula of the first iron phosphate precursor is Fe 0.973 PO4;
[0018] The chemical formula of the second iron phosphate precursor is Fe 0.965 PO4.
[0019] Preferably, in step (1), the mass ratio of the first iron phosphate precursor to the second iron phosphate precursor is 1:(2.67-4), wherein 2.67-4 can be 2.67, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4, etc.
[0020] Preferably, in step (1), the solid content of the first slurry and the second slurry is independently 20%-40%, for example, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, etc.
[0021] Preferably, the first lithium source and the second lithium source each independently comprise a eutectic lithium salt.
[0022] In the technical solution of the implementation mode of the present application, eutectic lithium salt is used as the first lithium source and the second lithium source; the eutectic lithium salt can not only reduce the temperature of the sintering treatment, but also has good fluidity in the molten state, and can fully contact with the first iron phosphate precursor and the second iron phosphate precursor, thereby improving the uniformity of mixing of the components of the positive electrode active material and improving the reaction efficiency; in addition, the eutectic lithium salt can accelerate the diffusion rate of active ions, help improve the kinetic process of the battery, achieve rapid reaction, and improve the electrochemical performance of the battery.
[0023] In addition, highly crystalline materials can be obtained with eutectic lithium salts. The higher the crystallinity of the material, the more regular and orderly the material synthesis is. High crystallinity is conducive to the diffusion of lithium ions inside the crystal. During the charging and discharging process of lithium iron phosphate, lithium ions need to shuttle back and forth in the lattice. High crystallinity means that there are more regular channels and smaller lattice distortion inside the crystal, and lithium ions can move more smoothly in these channels.
[0024] For example, in some experiments, it was found that lithium iron phosphate materials with good crystallinity have a higher lithium ion diffusion coefficient than materials with low crystallinity, which helps to improve the charge and discharge rate performance of the battery and enables the battery to be charged and discharged quickly at high currents. Lithium iron phosphate materials with high crystallinity generally have better capacity retention. Due to their stable structure, they can better resist volume changes and structural damage of the material during battery cycling. When the battery is repeatedly charged and discharged, the lattice of the lithium iron phosphate material will experience a certain degree of expansion and contraction. Materials with high crystallinity can better withstand such changes, reduce the loss of active materials, and thus maintain a higher battery capacity. For example, after multiple charge and discharge cycles, the capacity decay of lithium iron phosphate electrode materials with high crystallinity is relatively small, and they can maintain good electrochemical performance. Lithium iron phosphate materials with high crystallinity are more stable in thermal environments. Their regular crystal structure can withstand higher temperatures without decomposition or phase change. Thermal stability is very important during battery use, especially in some high power output or high temperature environments. For example, when the battery is working in a high temperature environment, lithium iron phosphate materials with high crystallinity can effectively avoid material decomposition and performance deterioration caused by increased temperature, thereby improving the safety and reliability of the battery. In the material synthesis process, high crystallinity often means better consistency and uniformity of the material. Whether in small-batch synthesis in the laboratory or large-scale industrial production, lithium iron phosphate materials with high crystallinity have smaller differences between particles. This is crucial to the overall performance of the battery, because if the crystallinity of the material is inconsistent, the electrochemical and thermal properties between different particles will vary greatly, thus affecting the overall performance of the battery pack. For example, when preparing lithium iron phosphate positive electrode materials, by optimizing the synthesis process to obtain materials with high crystallinity, it can be ensured that each particle has similar properties, making the battery performance more stable and predictable.
[0025] Preferably, the eutectic lithium salt includes any one of 0.38LiOH-0.62LiNO3, 0.37LiOH-0.63LiCl, 0.74LiOH-0.26Li2CO3, 0.71LiNO3-0.29LiCl or 0.55LiI-0.45LiOH, or a combination of at least two thereof.
[0026] In the present application, eutectic lithium salt refers to a crystalline material formed by two or more different molecules in a fixed stoichiometric ratio through non-ionic bonds and non-covalent bonds; taking 0.38LiOH-0.62LiNO3 as an example, it refers to a composition of LiOH and LiNO3 with a molar ratio of 0.38:0.62, and other similar expressions are the same.
[0027] Preferably, in step (1), the molar ratio of Li:Fe in the first slurry and the second slurry is independently 1:1.01 to 1.05; for example, 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, etc.
[0028] Preferably, the first carbon source and the second carbon source each independently include any one of glucose, sucrose or starch, or a combination of at least two of them.
[0029] Preferably, based on 100% of the mass of the first ferric phosphate precursor, the mass content of the first carbon source is 5%-15%, for example, 5%, 6%, 8%, 10%, 12%, 14%, 15%, etc.
[0030] Preferably, based on 100% of the mass of the second ferric phosphate precursor, the mass content of the second carbon source is 5%-15%, for example, 5%, 6%, 8%, 10%, 12%, 14%, 15%, etc.
[0031] Preferably, the first conductive agent and the second conductive agent each independently comprise a three-dimensional conductive agent.
[0032] In the technical solution of the implementation mode of the present application, the first conductive agent and the second conductive agent are preferably three-dimensional conductive agents. The reason is that the three-dimensional conductive agent has good conductivity and a multi-level pore structure (micropores, mesopores and macropores are interconnected), which can provide a fast electron transmission channel, thereby making the powder resistivity of the positive electrode active material lower, which is beneficial to reducing the polarization of the positive electrode active material in lithium battery applications.
[0033] As an example, the three-dimensional conductive agent includes any one of 3D porous graphene, 3D graphene foam, 3D carbon aerogel, 3D nitrogen-doped graphene network or 3D conductive polymer gel, or a combination of at least two thereof.
[0034] As an example, taking the mass of the first iron phosphate precursor as 100%, the mass content of the first conductive agent is 1%-4%, for example, 1%, 1.5%, 2%, 2.5%, 3%, 4%, etc.
[0035] As an example, based on the mass of the second iron phosphate precursor being 100%, the mass content of the second conductive agent is 1%-4%, for example, 1%, 1.5%, 2%, 2.5%, 3%, 4%, etc.
[0036] Preferably, the first slurry and the second slurry each independently further comprise a dispersant and / or an additive.
[0037] In the present application, the dispersant may be any material known in the art. For example, the dispersant includes any one of polyethylene glycol (PEG), polyvinyl alcohol (PVA), polyacrylamide (PAM) or oxalic acid, or a combination of at least two thereof.
[0038] In the present application, the additive may be any material known in the art. For example, the additive includes any one of ammonium titanium oxalate, tantalum ethoxide, vanadium pentoxide, magnesium phosphate, and phosphoric acid, or a combination of at least two of them.
[0039] In the present application, the added amounts of dispersants and additives can be designed according to needs.
[0040] As an example, taking the mass of the first iron phosphate precursor as 100%, in the first slurry, the mass content of the dispersant is 1%-4% (for example, 1%, 1.5%, 2%, 2.5%, 3%, 4%, etc.), and the mass content of the additive is 1%-4% (for example, 1%, 1.5%, 2%, 2.5%, 3%, 4%, etc.).
[0041] As an example, taking the mass of the second iron phosphate precursor as 100%, in the second slurry, the mass content of the dispersant is 1%-4% (for example, 1%, 1.5%, 2%, 2.5%, 3%, 4%, etc.), and the mass content of the additive is 1%-4% (for example, 1%, 1.5%, 2%, 2.5%, 3%, 4%, etc.).
[0042] Preferably, the sintering process includes low-temperature sintering, first pulverization, pulse high-temperature sintering and second pulverization.
[0043] In the technical solution of the implementation mode of the present application, during the sintering process, low-temperature sintering and the first crushing are first carried out to achieve uniform dispersion and coating of carbon and metal oxides; at the same time, it contributes to better contact and synchronous growth between particles during subsequent pulse high-temperature sintering, thereby preventing abnormal grain growth and obtaining a positive electrode active material with a high degree of grading, densification and high compaction density.
[0044] Pulse high temperature sintering is a rapid sintering method that helps maintain the material structure and reduce abnormal grain growth, thereby obtaining a uniform, high-density, and densified sintered body.
[0045] The role of the second crushing is to better improve the ion diffusion dynamics and the performance and maintenance of capacity.
[0046] As an example, the sintering process is performed under an inert atmosphere, such as a nitrogen and / or argon atmosphere.
[0047] Preferably, the heating rate of the low temperature sintering is 2.5-3°C / min, for example, 2.5°C / min, 2.6°C / min, 2.7°C / min, 2.8°C / min, 2.9°C / min, 3.0°C / min, etc.
[0048] Preferably, the temperature of the low-temperature sintering is 450°C to 550°C, for example, 450°C, 460°C, 480°C, 500°C, 520°C, 540°C, 550°C, etc.
[0049] Preferably, the low-temperature sintering time is 4 h to 6 h, for example, 4 h, 4.2 h, 4.4 h, 4.6 h, 4.8 h, 5 h, 5.2 h, 5.4 h, 5.6 h, 5.8 h, 6 h, etc.
[0050] Preferably, after the first pulverization, the Dv50 particle size of the obtained positive electrode active material is 0.7μm to 0.9μm, for example, 0.7μm, 0.72μm, 0.74μm, 0.76μm, 0.78μm, 0.8μm, 0.82μm, 0.84μm, 0.86μm, 0.88μm, 0.9μm, etc.
[0051] In the technical solution of the implementation mode of the present application, after the first pulverization, the Dv50 particle size of the obtained positive electrode active material is within the above range; in addition to better promoting the growth of particles and the adhesion between particles during the sintering process, it can also promote the uniformity, stability and crystallinity of the particles after subsequent high-temperature sintering to optimize performance; if the particle size is too high, it will lead to unevenness of the subsequent high-temperature sintering particles; if the particle size is too low, it will lead to serious agglomeration of particles after high-temperature sintering.
[0052] Preferably, the temperature of the pulse high temperature sintering is 750-770°C, for example, 750, 755°C, 760°C, 765°C, 770°C, etc.
[0053] In this application, pulse high temperature sintering refers to spark plasma sintering, which is a new type of rapid sintering technology that uses pulse energy, discharge pulse pressure and instantaneous high temperature field generated by Joule heat to achieve the sintering process, with a heating rate of 400℃ / s to 600℃ / s; for example, 400℃ / s, 450℃ / s, 500℃ / s, 550℃ / s, 600℃ / s, etc.
[0054] Preferably, the pulse high temperature sintering time is 2 h to 4 h, for example, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h, 4 h, etc.
[0055] Preferably, after the second pulverization, the Dv50 particle size of the obtained positive electrode active material is 1.1μm to 1.3μm, for example, 1.1μm, 1.12μm, 1.14μm, 1.16μm, 1.18μm, 1.2μm, 1.22μm, 1.24μm, 1.26μm, 1.28μm, 1.3μm, etc.
[0056] In the technical solution of the implementation mode of the present application, after the second crushing, the Dv50 particle size of the obtained positive electrode active material is within the above range; it can have a higher compaction density and at the same time can better exert its electrochemical performance; if the particle size is too high, it will lead to low discharge specific capacity; if the particle size is too low, it will lead to low compaction density.
[0057] As a preferred technical solution, the preparation method comprises the following steps:
[0058] (1) mixing a first iron phosphate precursor, a first lithium source, a first carbon source, a first conductive agent, a dispersant, and an additive to form a first slurry;
[0059] Mixing a second iron phosphate precursor, a second lithium source, a second carbon source, a second conductive agent, a dispersant and an additive to form a second slurry;
[0060] The primary particle size of the first iron phosphate precursor is 100 nm to 110 nm;
[0061] The primary particle size of the second iron phosphate precursor is 40nm to 100nm;
[0062] The first lithium source and the second lithium source each independently include a eutectic lithium salt;
[0063] (2) grinding the first slurry and the second slurry independently until the Dv50 particle size of the solid matter in the first slurry is 0.65 μm to 0.75 μm, and the Dv50 particle size of the solid matter in the second slurry is 0.20 μm to 0.30 μm;
[0064] (3) mixing the ground first slurry and the second slurry, spray drying and sintering to obtain the positive electrode active material;
[0065] Specifically, the sintering process includes low-temperature sintering, first pulverization, pulse high-temperature sintering and second pulverization;
[0066] After the first pulverization, the Dv50 particle size of the obtained positive electrode active material is 0.7 μm to 0.9 μm;
[0067] The pulse high temperature sintering temperature is 750°C to 770°C, and the pulse high temperature sintering time is 2h to 4h;
[0068] After the second pulverization, the Dv50 particle size of the obtained positive electrode active material is 1.1 μm to 1.3 μm.
[0069] In a second aspect, the present application provides a positive electrode active material, wherein the positive electrode active material is obtained by the preparation method described in the first aspect.
[0070] In a third aspect, the present application provides a battery, comprising the positive electrode active material obtained by the preparation method described in the first aspect, or the positive electrode active material described in the second aspect.
[0071] Compared with the prior art, the technical solution of this application has at least the following advantages:
[0072] The preparation method described in the present application is conducive to obtaining a positive electrode active material with a high compaction density, and the obtained positive electrode active material can improve the electrochemical performance of the battery.
[0073] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0075] Figure 1 This is a SEM image of the positive electrode active material prepared in Example 1 of the present invention;
[0076] Figure 2 This is a volume distribution diagram of the positive electrode active material prepared in Example 1 of the present invention;
[0077] Figure 3 A graph showing the volume ratio of primary particles of the positive electrode active material prepared in Example 1 of the present invention; DETAILED DESCRIPTION
[0078] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0079] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0080] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0081] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0082] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "2-10" means that all real numbers between "2-10" are listed in this document, and "2-10" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0083] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0084] Example 1
[0085] This embodiment provides a method for preparing a positive electrode active material, the preparation method comprising the following steps:
[0086] S1, select the second iron phosphate precursor (chemical formula is Fe 0.965 PO4, primary particle size of 40nm to 100nm) and the first iron phosphate precursor (chemical formula Fe 0.973 PO4, primary particle size is 100nm ~ 110nm), respectively add 0.38LiOH-0.62LiNO3 eutectic lithium salt, glucose (accounting for 10% of the mass of the iron phosphate precursor), 3D porous graphene (accounting for 1.5% of the mass of the iron phosphate precursor), PEG (accounting for 1.5% of the mass of the iron phosphate precursor), ammonium titanium oxalate (accounting for 1.5% of the mass of the iron phosphate precursor), and stir evenly with deionized water as solvent to obtain a first slurry with a solid content of 30% and a second slurry with a solid content of 30%; wherein the molar ratio of Li and Fe elements in the first slurry and the second slurry is each independently 1:1.02.
[0087] S2. After the first slurry and the second slurry are coarsely ground and sand-ground respectively, the Dv50 particle size of the first slurry is 0.70 μm, and the Dv50 particle size of the second slurry is 0.20 μm.
[0088] S3, mixing the first slurry and the second slurry, spray drying the obtained mixed slurry and collecting dry powder.
[0089] S4. The collected dry powder was sintered at low temperature for 4 h at a heating rate of 2.6°C / min to 500°C in a nitrogen atmosphere.
[0090] S5. The powder obtained in S4 is subjected to air flow milling until Dv50 is 0.8 μm.
[0091] S6. The powder obtained in S5 is subjected to pulse high temperature sintering in a nitrogen atmosphere at a heating rate of 500°C / s to a temperature of 760°C and sintered for 3 hours.
[0092] S7, the powder obtained in S6 is subjected to air flow pulverization, and the Dv50 is 1.2 μm, and then further demagnetized and sieved to obtain a lithium iron phosphate material with high specific energy, i.e., the positive electrode active material.
[0093] Example 2
[0094] This embodiment provides a method for preparing a positive electrode active material, the preparation method comprising the following steps:
[0095] S1, select the second iron phosphate precursor (chemical formula is Fe 0.965 PO4, primary particle size of 40 to 100 nm) and a first iron phosphate precursor (chemical formula Fe 0.973 PO4, primary particle size of 100-110nm), 0.38LiOH-0.62LiNO3 eutectic lithium salt, glucose (accounting for 10% of the mass of iron phosphate), 3D porous graphene (accounting for 1.5% of the mass of iron phosphate), PEG (accounting for 1.5% of the mass of iron phosphate), ammonium titanium oxalate (accounting for 1.5% of the mass of iron phosphate) were added respectively, and after stirring evenly with deionized water as solvent, a first slurry with a solid content of 30% and a second slurry with a solid content of 30% were obtained; wherein the molar ratio of Li and Fe elements in the first slurry and the second slurry was independently 1:1.02.
[0096] S2. After the first slurry and the second slurry are coarsely ground and sand-ground respectively, the Dv50 particle size of the first slurry is 0.70 μm, and the Dv50 particle size of the second slurry is 0.20 μm.
[0097] S3, mixing the first slurry and the second slurry, spray drying the obtained mixed slurry and collecting dry powder.
[0098] S4. The collected dry powder was sintered at 500°C for 4 h at a heating rate of 2.6°C / min under a nitrogen atmosphere.
[0099] S5. The powder obtained in S4 is subjected to air flow milling until Dv50 is 0.8 μm.
[0100] S6. The powder obtained in S5 is subjected to pulse high temperature sintering in an argon atmosphere at a heating rate of 500°C / s to a temperature of 760°C and sintering for 3 hours.
[0101] S7, the powder obtained in S6 is subjected to air flow pulverization, and the Dv50 is 1.2 μm, and then further demagnetized and sieved to obtain a lithium iron phosphate material with high specific energy, i.e., the positive electrode active material.
[0102] Example 3
[0103] This embodiment provides a method for preparing a positive electrode active material, the preparation method comprising the following steps:
[0104] S1, select the second iron phosphate precursor (chemical formula is Fe 0.965PO4, primary particle size of 40 to 100 nm) and a first iron phosphate precursor (chemical formula Fe 0.973 PO4, primary particle size is 100-110nm), 0.38LiOH-0.62LiNO3 eutectic lithium salt, glucose (accounting for 10% of the mass of iron phosphate), 3D porous graphene (accounting for 1.5% of the mass of iron phosphate), PEG (accounting for 1.5% of the mass of iron phosphate), ammonium titanium oxalate (accounting for 1.5% of the mass of iron phosphate) are added respectively, and after stirring evenly with deionized water as solvent, a first slurry with a solid content of 30% and a second slurry with a solid content of 30% are obtained; wherein the molar ratio of Li and Fe elements in the first slurry and the second slurry is each independently 1:1.02.
[0105] S2. After the first slurry and the second slurry are coarsely ground and sand-ground respectively, the Dv50 particle size of the first slurry is 0.70 μm, and the Dv50 particle size of the second slurry is 0.20 μm.
[0106] S3, mixing the first slurry and the second slurry, spray drying the obtained mixed slurry and collecting the dry powder.
[0107] S4. The collected dry powder was sintered at 500°C for 4 h at a heating rate of 2.6°C / min under a nitrogen atmosphere.
[0108] S5. The powder obtained in S4 is subjected to air flow milling until Dv50 is 0.8 μm.
[0109] S6. The powder obtained in S5 is subjected to pulse high temperature sintering in an argon atmosphere at a heating rate of 500°C / s to a temperature of 760°C and sintered for 3 hours.
[0110] S7, the powder obtained in S6 is subjected to air flow pulverization, and the Dv50 is 1.2 μm, and then further demagnetized and sieved to obtain a lithium iron phosphate material with high specific energy, i.e., the positive electrode active material.
[0111] Example 4
[0112] This embodiment provides a method for preparing a positive electrode active material, the preparation method comprising the following steps:
[0113] S1, select the second iron phosphate precursor (chemical formula is Fe 0.965 PO4, primary particle size of 40 to 100 nm) and a first iron phosphate precursor (chemical formula Fe 0.973PO4, primary particle size is 100-110nm), 0.74LiOH-0.26Li2CO3 eutectic lithium salt, glucose (accounting for 10% of the mass of iron phosphate), 3D porous graphene (accounting for 1.5% of the mass of iron phosphate), PEG (accounting for 1.5% of the mass of iron phosphate), ammonium titanium oxalate (accounting for 1.5% of the mass of iron phosphate) are added respectively, and after stirring evenly with deionized water as solvent, a first slurry with a solid content of 30% and a second slurry with a solid content of 30% are obtained; wherein the molar ratio of Li and Fe elements in the first slurry and the second slurry is each independently 1:1.02.
[0114] S2. After the first slurry and the second slurry are coarsely ground and sand-ground respectively, the Dv50 particle size of the first slurry is 0.65 μm, and the Dv50 particle size of the second slurry is 0.25 μm.
[0115] S3, mixing the first slurry and the second slurry, spray drying the obtained mixed slurry and collecting dry powder.
[0116] S4. The collected dry powder was sintered at 500°C for 4 h at a heating rate of 2.6°C / min under a nitrogen atmosphere.
[0117] S5. The powder obtained in S4 is subjected to air flow milling until Dv50 is 0.8 μm.
[0118] S6. The powder obtained in S5 is subjected to pulse high temperature sintering in an argon atmosphere at a heating rate of 2.6°C / min to a temperature of 770°C and sintered for 2h.
[0119] S7. The powder obtained in S6 is subjected to air flow pulverization, and the Dv50 is 1.1 μm. The powder is further demagnetized and sieved to obtain a lithium iron phosphate material with high specific energy, i.e., the positive electrode active material.
[0120] Example 5
[0121] This embodiment provides a method for preparing a positive electrode active material, the preparation method comprising the following steps:
[0122] S1, select the second iron phosphate precursor (chemical formula is Fe 0.965 PO4, primary particle size of 40 to 100 nm) and a first iron phosphate precursor (chemical formula Fe 0.973PO4, primary particle size of 100-110nm), 0.38LiOH-0.62LiNO3 mixed eutectic lithium salt, glucose (accounting for 10% of the mass of iron phosphate), 3D graphene foam (accounting for 1.5% of the mass of iron phosphate), PEG (accounting for 1.5% of the mass of iron phosphate), ammonium titanium oxalate (accounting for 1.5% of the mass of iron phosphate) were added respectively, and after stirring evenly with deionized water as solvent, a first slurry with a solid content of 30% and a second slurry with a solid content of 30% were obtained; wherein the molar ratio of Li and Fe elements in the first slurry and the second slurry was each independently 1:1.02.
[0123] S2. After the first slurry and the second slurry are coarsely ground and sand-ground respectively, the Dv50 particle size of the first slurry is 0.65 μm, and the Dv50 particle size of the second slurry is 0.25 μm.
[0124] S3, mixing the first slurry and the second slurry, spray drying the obtained mixed slurry and collecting dry powder.
[0125] S4. The collected dry powder was sintered at 500° C. for 4 h at a heating rate of 2.6° C. / min under a nitrogen atmosphere.
[0126] S5. The powder obtained in S4 is subjected to air flow milling until Dv50 is 0.8 μm.
[0127] S6. The powder obtained in S5 is subjected to pulse high temperature sintering in an argon atmosphere at a heating rate of 500°C / s to a temperature of 770°C and sintered for 2h.
[0128] S7. The powder obtained in S6 is subjected to air flow pulverization, and the Dv50 is 1.1 μm. The powder is further demagnetized and sieved to obtain a lithium iron phosphate material with high specific energy, i.e., the positive electrode active material.
[0129] Example 6
[0130] This embodiment provides a method for preparing a positive electrode active material, the preparation method comprising the following steps:
[0131] S1, select the second iron phosphate precursor (chemical formula is Fe 0.965 PO4, primary particle size of 40 to 100 nm) and a first iron phosphate precursor (chemical formula Fe 0.973PO4, primary particle size is 100-110nm), 0.38LiOH-0.62LiNO3 mixed eutectic lithium salt, glucose (accounting for 10% of the mass of iron phosphate), 3D graphene foam (accounting for 1.5% of the mass of iron phosphate), PEG (accounting for 1.5% of the mass of iron phosphate), tantalum pentoxide (accounting for 1.5% of the mass of iron phosphate) are added respectively, and after stirring evenly with deionized water as solvent, a first slurry with a solid content of 30% and a second slurry with a solid content of 30% are obtained; wherein the molar ratio of Li and Fe elements in the first slurry and the second slurry is each independently 1:1.02.
[0132] S2. After the first slurry and the second slurry are coarsely ground and sand-ground respectively, the Dv50 particle size of the first slurry is 0.65 μm, and the Dv50 particle size of the second slurry is 0.25 μm.
[0133] S3, mixing the first slurry and the second slurry, spray drying the obtained mixed slurry and collecting dry powder.
[0134] S4. The collected dry powder was sintered at 500° C. for 4 h at a heating rate of 2.6° C. / min under a nitrogen atmosphere.
[0135] S5. The powder obtained in S4 is subjected to air flow milling until Dv50 is 0.8 μm.
[0136] S6. The powder obtained in S5 is subjected to pulse high temperature sintering in an argon atmosphere at a heating rate of 500°C / s to a temperature of 750°C and sintered for 4 hours.
[0137] S7. The powder obtained in S6 is subjected to air flow pulverization, and the Dv50 is 1.1 μm. The powder is further demagnetized and sieved to obtain a lithium iron phosphate material with high specific energy, i.e., the positive electrode active material.
[0138] Example 7
[0139] The difference between this embodiment and embodiment 1 is that the 0.38LiOH-0.62LiNO3 eutectic lithium salt is replaced by an equal molar amount of LiOH, and the rest is the same as embodiment 1.
[0140] Example 8
[0141] The difference between this embodiment and embodiment 1 is that the mass ratio of the second iron phosphate precursor to the first iron phosphate precursor is 5:1, and the rest is the same as embodiment 1.
[0142] Example 9
[0143] The difference between this embodiment and embodiment 1 is that the mass ratio of the first iron phosphate precursor to the second iron phosphate precursor is 1:1, and the rest is the same as embodiment 1.
[0144] Example 10
[0145] The difference between this embodiment and embodiment 1 is that the first crushing is not included after low-temperature sintering, and the rest is the same as embodiment 1.
[0146] Embodiment 11
[0147] The difference between this embodiment and embodiment 1 is that the first crushing is performed to a Dv50 particle size of 1.1 μm, and the rest is the same as embodiment 1.
[0148] Example 12
[0149] The difference between this embodiment and embodiment 1 is that the first crushing is performed to a Dv50 particle size of 0.5 μm, and the rest is the same as embodiment 1.
[0150] Embodiment 13
[0151] The difference between this embodiment and embodiment 1 is that the second crushing is performed to a Dv50 particle size of 1.5 μm, and the rest is the same as embodiment 1.
[0152] Embodiment 14
[0153] The difference between this embodiment and embodiment 1 is that the second crushing is performed to a Dv50 particle size of 0.9 μm, and the rest is the same as embodiment 1.
[0154] Embodiment 15
[0155] The difference between this embodiment and embodiment 1 is that the sintering process is directly replaced by sintering at 750° C. for 10 h, and the rest is the same as embodiment 1.
[0156] Comparative Example 1
[0157] The difference between this comparative example and Example 1 is that the first iron phosphate precursor and the second iron phosphate precursor are used to prepare lithium iron phosphate respectively, and then the lithium iron phosphate prepared from the second iron phosphate precursor and the lithium iron phosphate prepared from the first iron phosphate precursor are mixed in a mass ratio of 4:1, and the rest is the same as Example 1.
[0158] Comparative Example 2
[0159] The difference between this comparative example and Example 1 is that the first slurry is ground to a Dv50 particle size of 0.9 μm, and the rest is the same as Example 1.
[0160] Comparative Example 3
[0161] The difference between this comparative example and Example 1 is that the first slurry is ground to a Dv50 particle size of 0.5 μm, and the rest is the same as Example 1.
[0162] Comparative Example 4
[0163] The difference between this comparative example and Example 1 is that the second slurry is ground to a Dv50 particle size of 0.4 μm, and the rest is the same as Example 1.
[0164] Comparative Example 5
[0165] The difference between this comparative example and Example 1 is that the second slurry is ground to a Dv50 particle size of 0.1 μm, and the rest is the same as Example 1.
[0166] Ⅰ. Physical performance test
[0167] (1) Morphology test: Taking Example 1 as an example, the prepared positive electrode active material was subjected to morphology test by scanning electron microscopy (SEM). Figure 1 As shown, the results show that the positive electrode active material prepared in the present application has good morphology, no excessive agglomeration, and presents obvious size particle gradation.
[0168] Taking Example 1 as an example, the prepared positive electrode active material was tested for particle size by a Malvern laser particle size analyzer. Figure 2 and Figure 3 As shown, the results show that the positive electrode active material prepared in the present application has a higher degree of gradation.
[0169] (2) Compacted density: Slowly pour about 0.62 g of dried lithium iron phosphate powder into a mold. Then place the mold in a pre-vibration instrument and vibrate it fifteen times. Then test it in a powder compaction density instrument.
[0170] (3) Powder resistance: After the lithium iron phosphate powder is pressed into a thin sheet of a certain shape, it is placed on a four-probe tester for testing.
[0171] (4) Carbon content: Weigh 15 mg of lithium iron phosphate sample and place the sample in a clean crucible. Place the crucible containing the sample into the heating furnace of the thermogravimetric analyzer. Set an appropriate heating rate to test the carbon content of lithium iron phosphate.
[0172] The test results are summarized in Table 1.
[0173] Table 1
[0174] <![CDATA[Compaction density (g / cm 3 , 3T)]]> Powder resistance (Ω·cm) Carbon content (%) Example 1 2.642 13.6 1.325 Example 2 2.623 14.1 1.345 Example 3 2.621 13.9 1.346 Example 4 2.638 13.7 1.327 Example 5 2.632 13.8 1.326 Example 6 2.635 13.9 1.329 Example 7 2.628 14.5 1.329 Example 8 2.651 14.6 1.325 Example 9 2.491 14.3 1.327 Example 10 2.619 14.6 1.341 Embodiment 11 2.618 14.9 1.343 Example 12 2.615 14.8 1.345 Embodiment 13 2.621 15.2 1.356 Embodiment 14 2.569 14.3 1.343 Embodiment 15 2.529 16.1 1.389 Comparative Example 1 2.463 15.3 1.358 Comparative Example 2 2.513 15.4 1.368 Comparative Example 3 2.496 15.7 1.412 Comparative Example 4 2.489 15.6 1.423 Comparative Example 5 2.425 15.5 1.428
[0175] II. Electrochemical Performance
[0176] The positive electrode active materials of each embodiment and comparative example are prepared into positive electrode sheets, and the specific process is as follows:
[0177] The positive electrode active material, conductive agent (SP), and binder (PVDF) are mixed in a mass ratio of 92:4:4 to obtain positive electrode slurry; then, the positive electrode slurry is evenly coated on aluminum foil, vacuum-treated at 110°C overnight, cut into small pieces, and then assembled into a half-cell in an argon glove box, using metallic lithium as the counter electrode and Xinzhoubang LBC305-1 as the electrolyte. The assembled button cell is of CR2016 type and charged and discharged in constant current charge and discharge mode.
[0178] (1) 0.1C charge specific capacity: Place the test sample in a 25℃ constant temperature box and let it stand for 10 hours. Set the charge current to 0.1C on the Xinwei charge and discharge tester, and set the charge cut-off current to 0.01C. The charge cut-off voltage is 3.75V.
[0179] After the voltage is charged to 3.75V and stabilized, read the data from the instrument.
[0180] (2) 0.1C discharge specific capacity: Data when (1) is discharged from 3.75V to 2.0V at 0.1C constant voltage.
[0181] (3) First coulombic efficiency: the ratio of 0.1C discharge specific capacity to 0.1C charge specific capacity.
[0182] (4) 1C discharge specific capacity: Place the test sample in a 25℃ constant temperature box and let it stand for 10 hours. Set the charging current to 0.1C on the Xinwei charge and discharge tester, and at the same time, set the charging cut-off current to 0.01C. The charging cut-off voltage is 3.75V. After the voltage is charged to 3.75V and stabilizes, it is discharged at a constant voltage of 0.1C to 2.0V. After the above cycle is repeated three times, set the charging current to 1C, and at the same time, set the charging cut-off current to 0.1C. The charging cut-off voltage is 3.75V. After the voltage is charged to 3.75V and stabilizes, it is discharged at a constant voltage of 1C to 2.0V.
[0183] (5) 5C discharge specific capacity: Place the test sample in a 25℃ constant temperature box and let it stand for 10 hours. Set the charging current to 0.1C on the Xinwei charge and discharge tester, and at the same time, set the charging cut-off current to 0.01C. The charging cut-off voltage is 3.75V. After the voltage is charged to 3.75V and stabilizes, it is discharged at a constant voltage of 0.1C to 2.0V. After the above cycle is repeated three times, set the charging current to 5C, and at the same time, set the charging cut-off current to 0.5C. The charging cut-off voltage is 3.75V. After the voltage is charged to 3.75V and stabilizes, it is discharged at a constant voltage of 5C to 2.0V.
[0184] The test results are summarized in Table 2.
[0185] Table 2
[0186]
[0187]
[0188] Combined with Table 1 and Table 2, the examples and comparative examples are analyzed as follows:
[0189] It can be seen from Comparative Example 1 and Example 1 that the compaction density of Comparative Example 1 is lower and the electrochemical performance is poor, which proves that the preparation method of the present application, in which the first slurry and the second slurry are mixed to prepare the positive electrode active material, is more conducive to improving the electrochemical performance of the battery while preparing the positive electrode active material with excellent compaction density.
[0190] It can be seen from Comparative Examples 2-3 and Example 1 that the compaction density of Comparative Examples 2-3 is lower and the electrochemical performance is poor, which proves that grinding the first slurry to a Dv50 particle size within the preferred range is more conducive to preparing a positive electrode active material with excellent compaction density while improving the electrochemical performance of the battery.
[0191] It can be seen from Comparative Examples 4-5 and Example 1 that the compaction density of Comparative Examples 4-5 is lower and the electrochemical performance is poor, which proves that grinding the second slurry to a Dv50 particle size within the preferred range is more conducive to improving the electrochemical performance of the battery while preparing a positive electrode active material with excellent compaction density.
[0192] It can be seen from Example 7 and Example 1 that although the compaction density of Example 7 is similar to that of Example 1, the electrochemical performance of Example 7 is not as good as that of Example 1, which proves that the use of eutectic lithium salt as the first lithium source and / or the second lithium source is more conducive to improving the electrochemical performance of the battery while preparing a positive electrode active material with excellent compaction density.
[0193] It can be seen from Examples 8-9 and Example 1 that although the compaction density of Example 8 is greater than that of Example 1, the electrochemical performance of Example 8 is not as good as that of Example 1; although the electrochemical performance of Example 9 is worse than that of Example 1, the compaction density of Example 9 is lower than that of Example 1; it is proved that using a mass ratio of the first iron phosphate precursor to the second iron phosphate precursor in the range of 1:(2.67~4) is more conducive to improving the electrochemical performance of the battery while preparing a positive electrode active material with excellent compaction density.
[0194] It can be seen from Examples 10-12 that the compaction densities of Examples 10-12 are similar, but the electrochemical performance is poor, which proves that crushing the material after low-temperature sintering so that the Dv50 particle size is within the preferred range is more conducive to preparing positive electrode active materials with excellent compaction density while improving the electrochemical performance of the battery.
[0195] It can be seen from Examples 13-14 that the compaction densities of Examples 13-14 are similar, but the electrochemical performance is poor, which proves that crushing the material after pulse high-temperature sintering to make the Dv50 particle size within the preferred range is more conducive to preparing positive electrode active materials with excellent compaction density while improving the electrochemical performance of the battery.
[0196] Analysis of Example 15 shows that the compaction density and electrochemical performance of Example 15 are relatively poor, which proves that the sintering process of the present application is more conducive to improving the electrochemical performance of the battery while preparing a positive electrode active material with excellent compaction density.
[0197] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A method for preparing a positive electrode active material, characterized in that: The preparation method comprises the following steps: (1) mixing a first iron phosphate precursor, a first lithium source, a first carbon source and a first conductive agent to form a first slurry; Mixing a second iron phosphate precursor, a second lithium source, a second carbon source, and a second conductive agent to form a second slurry; The primary particle size of the first iron phosphate precursor is 100 nm to 110 nm; The primary particle size of the second iron phosphate precursor is 40nm to 100nm; (2) grinding the first slurry and the second slurry independently until the Dv50 particle size of the solid matter in the first slurry is 0.65 μm to 0.75 μm, and the Dv50 particle size of the solid matter in the second slurry is 0.20 μm to 0.30 μm; (3) After mixing the ground first slurry and the second slurry, spray drying and sintering are performed to obtain the positive electrode active material.
2. The preparation method according to claim 1, characterized in that: In step (1), the chemical formula of the first iron phosphate precursor is Fe 0.973 PO4; The chemical formula of the second iron phosphate precursor is Fe 0.965 PO4; Preferably, in step (1), the mass ratio of the first iron phosphate precursor to the second iron phosphate precursor is 1:(2.67-4); Preferably, in step (1), the solid content of the first slurry and the second slurry is independently 20%-40%.
3. The preparation method according to claim 1 or 2, characterized in that: The first lithium source and the second lithium source each independently include a eutectic lithium salt; Preferably, the eutectic lithium salt includes any one or a combination of at least two of 0.38LiOH-0.62LiNO3, 0.37LiOH-0.63LiCl, 0.74LiOH-0.26Li2CO3, 0.71LiNO3-0.29LiCl or 0.55LiI-0.45LiOH; Preferably, in step (1), the molar ratio of Li:Fe in the first slurry and the second slurry is independently 1:1.01 to 1.
05.
4. The preparation method according to claim 1, characterized in that: The first carbon source and the second carbon source each independently include any one of glucose, sucrose or starch, or a combination of at least two thereof; Preferably, based on 100% of the mass of the first iron phosphate precursor, the mass content of the first carbon source is 5%-15%; Preferably, based on 100% of the mass of the second iron phosphate precursor, the mass content of the second carbon source is 5%-15%; Preferably, the first conductive agent and the second conductive agent each independently comprise a three-dimensional conductive agent; Preferably, the first slurry and the second slurry each independently further comprise a dispersant and / or an additive.
5. The preparation method according to claim 1, characterized in that: The sintering process includes low-temperature sintering, first pulverization, pulse high-temperature sintering and second pulverization.
6. The preparation method according to claim 5, characterized in that: The heating rate of the low temperature sintering is 2.5°C / min to 3°C / min; Preferably, the temperature of the low temperature sintering is 450°C to 550°C; Preferably, the low temperature sintering time is 4h to 6h; Preferably, after the first pulverization, the Dv50 particle size of the obtained positive electrode active material is 0.7 μm to 0.9 μm.
7. The preparation method according to claim 5, characterized in that: The temperature of the pulse high temperature sintering is 750°C to 770°C; Preferably, the pulse high temperature sintering time is 2h to 4h; Preferably, after the second pulverization, the Dv50 particle size of the obtained positive electrode active material is 1.1 μm to 1.3 μm.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) mixing a first iron phosphate precursor, a first lithium source, a first carbon source, a first conductive agent, a dispersant, and an additive to form a first slurry; Mixing a second iron phosphate precursor, a second lithium source, a second carbon source, a second conductive agent, a dispersant, and an additive to form a second slurry; The primary particle size of the first iron phosphate precursor is 100 nm to 110 nm; The primary particle size of the second iron phosphate precursor is 40nm to 100nm; The first lithium source and the second lithium source each independently include a eutectic lithium salt; (2) grinding the first slurry and the second slurry independently until the Dv50 particle size of the solid matter in the first slurry is 0.65 μm to 0.75 μm, and the Dv50 particle size of the solid matter in the second slurry is 0.20 μm to 0.30 μm; (3) mixing the ground first slurry and the second slurry, spray drying and sintering to obtain the positive electrode active material; Specifically, the sintering process includes low-temperature sintering, first pulverization, pulse high-temperature sintering and second pulverization; After the first pulverization, the Dv50 particle size of the obtained positive electrode active material is 0.7 μm to 0.9 μm; The temperature of the pulse high temperature sintering is 750°C to 770°C, and the time of the pulse high temperature sintering is 2h to 4h; After the second pulverization, the Dv50 particle size of the obtained positive electrode active material is 1.1 μm to 1.3 μm.
9. A positive electrode active material, characterized in that: The positive electrode active material is obtained by the preparation method according to any one of claims 1 to 8.
10. A battery, characterized in that: The battery comprises the positive electrode active material obtained by the preparation method according to any one of claims 1 to 8, or the positive electrode active material according to claim 9.
Citation Information
Patent Citations
Method for manufacturing industrialized high-energy lithium iron phosphate material
CN102916179A
Lithium ferromanganese phosphate composites and lithium ion batteries
CN109192963A
High-compaction lithium iron phosphate material and preparation method thereof
CN111217347A
Lithium ion battery positive electrode material using eutectic lithium salt and preparation method of lithium ion battery positive electrode material
CN113707873A
Preparation method of single-crystal lithium nickel manganese oxide positive electrode material with exposed specific crystal face
CN116986645A